A Comprehensive Review of Sustainable Benefit of Cassava Starch and Its Potential in Wood-Based and Lignocellulosic Materials - Mohd Ghani, Ros Syazmini; Lee, Man Djun; Mohd Razali, Sofiyah (Journal of Emerging Technologies and Industrial Applications, 2023)
Cassava starch is an incredibly versatile material that can be used to create a diversity of practical and environmental friendly products apart from its primary application for the food industry. As a result, there has been a considerable effort towards developing various products from cassava starch in other industries like textile, pharmaceutical and cosmetics. The wood industry should also benefit from cassava starch properties like other industries. However, the application of cassava starch in the wood industry is still in the infancy stage. Therefore, many technical challenges need to be addressed to increase the practicality and application of the products so that they could be commercialized. This review paper provides up-to-date insight into cassava starch-wood-based products. The limitation and how to overcome them are highlighted in this paper. Additionally, new areas for future research are also being discussed. All in all, a review of works of literature found that cassava starch-wood-based products have great potential in wood adhesives and binders and thermoplastic starch (TPS) composite.